(untitled) (Boletín de Investigaciones Marinas y Costeras, 2016)
This paper collects bibliographic information about the Goblin shark, Mitsukurina owstoni (Chondrichthyes: Mitsukurinidae), an uncommon shark from deeper waters. One specimen of this species was captured near Nenguange bay and it is recorded for rst time in the Colombian Caribbbean.